Stabilizing the (003) Facet of Micron-Sized LiNi0.6Co0.2Mn0.2O2 Cathode Material Using Tungsten Oxide as an Exemplar - Yang Li; Liubin Ben; Hailong Yu; Wenwu Zhao; Xinjiang Liu; Xuejie Huang (Inorganics, 2022)
The structural stability of layered LiNi1-x-yCoxMnyO2 cathode materials is critical for guaranteeing their excellent electrochemical cycling performance, particularly at elevated temperatures. However, the notorious H2–H3 phase transition along with associated large changes in the c-axis or (003) facet is the fundamental origin of the anisotropic and abrupt change in the unit cell and the degradation of the cycling performance. In this study, we coat micron-sized LiNi0.6Co0.2Mn0.2O2 (NCM) with tungsten oxide via atomic layer deposition and investigate the atomic-to-microscopic structures in detail via advanced characterization techniques, such as Cs-corrected scanning transmission electron microscopy. The results reveal that coated tungsten oxide is predominately accumulated on the (003) facet of NCM, with the migration of a small amount of W6+ into this facet, resulting in a reduction of Ni3+ to Ni2+ and the formation of a rock-salt-like structure on the surface. The electrochemical cycling performance of tungsten-oxide-coated NCM is significantly improved, showing a capacity retention of 86.8% after 300 cycles at 55 °C, compared to only 69.4% for the bare NCM. Through further structural analysis, it is found that the initial tungsten-oxide-coating-induced (003) facet distortion effectively mitigates the expansion of the c-lattice during charge, as well as oxygen release from the lattice, resulting in a lowered strain in the cathode lattices and a crack in the cathode particles after prolonged cycling.